Evaluation of Antiplatelet Aggregation and Anticoagulant Effects of Oxalis Debilis Kunth Rhizome Extracts - Thi Van Anh, Nguyen; Ngoc Trang, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2024)
Cardiovascular disease is one of the leading causes of death globally. The discovery and use of natural products in the prevention and treatment of cardiovascular diseases have achieved great interest. Oxalis debilis is traditionally used for the treatment of various ailments.  This study aimed to investigate the potential antiplatelet and anticoagulant properties of extracts derived from O. debilis rhizome. The rhizome of O. debilis was extracted with methanol and then fractionated to obtain four extracts: the total methanol extract, the n -hexane, ethyl acetate, and water fraction. These four extracts were then tested for their ability to inhibit platelet aggregation and blood coagulation in human blood samples. This report demonstrated for the first time that O. debilis had inhibitory effects on platelet aggregation induced by both adenosine diphosphate and collagen as well as blood coagulation. Moreover, the total methanol extract, the ethyl acetate, and the water fraction had strong antiplatelet aggregation effects. All tested extracts had mild anticoagulant activities. This plant could be a valuable natural source for searching for antithrombotic substances, or for the development of supplementary products for the treatment and prevention of heart diseases and thrombosis.